Acrylate matrix for low-odor rock plate adhesive, rock plate adhesive and preparation method of acrylate matrix
By using a method of combining a high-functional acrylate matrix with a thiol-acrylate curing system, the existing rock sheet glue products have been solved, and the rock sheet glue with high odor, high bond strength and good water resistance are achieved.
Patent Information
- Application Number
- CN202411991827.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-29
AI Technical Summary
The existing rock sheet glue products have the disadvantages of large odor, low short-term bonding strength, poor resistance and short storage period, and there are many irritating substances evaporate during production and use.
A high-functional acrylate matrix was used to combine with a thiol-acrylate curing system, and a low-odor stone plate glue was prepared by reacting dipentaerythritol hexacrylate and an amine chain extender under heating conditions.
It achieves low odor, high short-term bonding strength, good water resistance, long storage period and good toughness, avoiding the use of volatile and irritating substances.
Smart Images

Figure SMS_9 
Figure SMS_10 
Figure SMS_11
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of rock slab glue, and in particular to an acrylic ester matrix for low-odor rock slab glue, the rock slab glue and a preparation method thereof. Background Art
[0002] Rock slab glue is an adhesive used for splicing and fixing rock slabs in rock slab processing plants. It has good application prospects. Due to the need to improve production efficiency, rock slab furniture needs to be moved out of the operating table as soon as possible after bonding. Rock slab processing plants usually have high requirements for short-term bonding strength.
[0003] Currently, the rock glue products on the market mainly include three categories: epoxy, acrylate and unsaturated polyester. Although epoxy rock glue has the advantages of high bonding strength and good aging resistance, it has defects such as low short-term bonding strength, strong odor and difficulty in construction at low temperatures; common acrylic rock glue has advantages such as high short-term bonding strength, but it has disadvantages such as strong odor, easy to soften and sticky surface, poor resistance and short storage period; unsaturated polyester glue has advantages such as high short-term bonding strength and low cost, but it also has disadvantages such as strong odor, easy to soften and sticky surface and short storage period. At the same time, the main rock glue products on the market have more irritating substances volatilized during the production and use process, such as methyl methacrylate, styrene and sulfide and other volatile irritating substances, which generally have the disadvantage of strong odor.
[0004] In view of this, the present invention is proposed. Summary of the invention
[0005] The present invention provides an acrylic ester matrix for low-odor rock slab glue, rock slab glue and a preparation method thereof, in order to solve the above-mentioned defects existing in the prior art.
[0006] Specifically, in a first aspect, the present invention provides a high-functionality acrylate matrix for a rock slab adhesive, wherein the rock slab adhesive adopts a thiol-acrylate curing system, which is obtained by reacting dipentaerythritol hexaacrylate and an amine chain extender under heating conditions; The amine chain extenders include ethanolamine and cyclohexanedimethylamine.
[0007] The thiol-acrylate curing system of the present invention is a system that achieves curing through the reaction between a thiol compound and an acrylate. In practical applications, the thiol-acrylate curing system can be applied to rock slab adhesive products to obtain rock slab adhesives with excellent performance. The high-functionality acrylate matrix for rock slab adhesives of the present invention refers to the use of a high-functionality acrylate matrix to configure the acrylate component in the thiol-acrylate curing system for reacting with thiol compounds.
[0008] Thiols are generally used for the rapid curing of epoxies. The thiol-epoxy curing system needs a tertiary amine accelerator to react quickly. Most of the thiol curing agents conventionally sold on the market have already added tertiary amine accelerators when they leave the factory, and have a very obvious sulfur odor. Thiol curing agents without added accelerators usually react very slowly. Tertiary amine accelerators can also cure epoxy, so they cannot be put in the same component as epoxy, and the odor cannot be reduced by adjusting the component of the accelerator. Therefore, the present invention adopts acrylate to react with thiol, adds tertiary amine to the acrylate component, and selects high molecular weight, accelerator-free, low-odor thiol, so that the rock slab glue has a lower odor as a whole. Using conventional acrylate components, the resulting rock slab glue has a very poor effect and is difficult to use.
[0009] Based on this, the present invention proposes a high-functionality acrylate matrix for the above-mentioned rock slab glue, and the acrylate matrix has good compatibility with the accelerator. More importantly, the high-functionality acrylate matrix for the rock slab glue is obtained by reacting an optimized amine chain extender and a specific hexafunctional acrylate. The structural design fully considers factors such as its stability as an acrylate component matrix, its influence on the curing rate of the thiol-acrylate curing system, and its compatibility with other components, and can take into account various application performances of the rock slab glue.
[0010] According to the high-functionality acrylate matrix provided by the present invention, the cyclohexanedimethylamine includes 1,4-cyclohexanedimethylamine; Preferably, the weight ratio of ethanolamine to cyclohexanedimethylamine is (4-5): (1-2); More preferably, the weight ratio of dipentaerythritol hexaacrylate, ethanolamine and cyclohexanedimethylamine is 100:4:2.
[0011] In the present invention, controlling the amount of each raw material within the above range is helpful to improve the application performance of the high-functionality acrylate matrix in the rock slab adhesive, especially taking into account both construction performance and mechanical properties.
[0012] The high-functionality acrylate matrix provided according to the present invention comprises one or a combination of two or more compounds having the structural formula R1-N(CH2-R2)2; R1 is selected from and / or ; R2 is selected from .
[0013] In the present invention, the reaction process of dipentaerythritol hexaacrylate and amine chain extender includes: R1-NH2+2CH2=R2→R1-N(CH2-R2)2.
[0014] When the amine chain extender is 1,4-cyclohexanedimethylamine, R1 of the compound is selected from .
[0015] When the amine chain extender is ethanolamine, R1 of the compound is selected from .
[0016] When the amine chain extender is a mixture of 1,4-cyclohexanedimethylamine and ethanolamine, the high-functionality acrylate matrix contains compounds of the above two structures.
[0017] The high-functionality acrylate matrix formed by chain extension of ethanolamine contains the compound shown in the following structure: .
[0018] The high-functionality acrylate matrix formed by chain extension of 1,4-cyclohexanedimethylamine contains the compound shown in the following structure: .
[0019] The present invention Indicates the attachment site of the corresponding functional group.
[0020] In a second aspect, the present invention also provides a method for preparing the high-functionality acrylate matrix as described above, comprising: reacting dipentaerythritol hexaacrylate and an amine chain extender under heating conditions; the amine chain extender comprises ethanolamine and cyclohexanedimethylamine.
[0021] Preferably, dipentaerythritol hexaacrylate is added into a reactor with a condensation reflux device, reacted under a nitrogen atmosphere, the reaction system is heated to 50° C., an amine chain extender is slowly added dropwise thereto, and the temperature is simultaneously raised to 50° C. to 60° C. and kept warm for 3 to 4 hours to obtain the high-functionality acrylate matrix.
[0022] In a third aspect, the present invention further provides a rock slab adhesive, which is obtained by mixing component A and component B and curing them, wherein component A includes an acrylate matrix and an accelerator; component B includes a thiol compound; and the accelerator includes a tertiary amine structure; The acrylate matrix comprises the high-functionality acrylate matrix as described above or the high-functionality acrylate matrix prepared by the preparation method as described above.
[0023] In the present invention, component A and component B of the rock slab adhesive can undergo Michael addition reaction under the above conditions.
[0024] The present invention adopts the high-functionality acrylate matrix of the above-mentioned specific structure, and by constructing a thiol-acrylate curing system, an acrylate rock slab adhesive with low odor, high short-term bonding strength, good water resistance, long storage period and good toughness can be obtained.
[0025] According to the rock slab adhesive provided by the present invention, the thiol compound includes pentaerythritol tetrakis(3-mercaptopropionate) and / or trimethylolpropane tris(mercaptopropionate); Preferably, the weight ratio of pentaerythritol tetrakis(3-mercaptopropionate) to trimethylolpropane tris(mercaptopropionate) is (50-64):(6-20).
[0026] According to the rock slab adhesive provided by the present invention, based on 100 parts by weight, component A includes: 55-70 parts of the high-functionality acrylate matrix, 0-10 parts of acrylate monomer, 1-4 parts of accelerator, 6-10 parts of diluent, 3-5 parts of the first thixotropic agent and the balance of the first filler; And / or, based on 100 parts by weight, component B includes 50-64 parts of pentaerythritol tetrakis(3-mercaptopropionate), 6-20 parts of trimethylolpropane tris(mercaptopropionate), 2-8 parts of the second thixotropic agent and the balance of the second filler.
[0027] According to the rock slab adhesive provided by the present invention, the acrylate monomer is selected from polypropylene glycol diacrylate; According to the rock slab glue provided by the present invention, the accelerator is selected from one or a combination of two or more of triethanolamine, triethylenediamine and N,N-dimethylcyclohexylamine; According to the rock slab glue provided by the present invention, the diluent is selected from one or a combination of two or more of nonylphenol, dodecylphenol and styrenated phenol; According to the rock slab glue provided by the present invention, the first filler is selected from nano calcium carbonate; According to the rock slab glue provided by the present invention, the first thixotropic agent is selected from hydrophobic fumed silica; According to the rock slab glue provided by the present invention, the second filler is selected from nano calcium carbonate; According to the rock slab glue provided by the present invention, the second thixotropic agent is selected from hydrophobic fumed silica.
[0028] The selected diluent provided by the present invention has a certain anti-aggregation effect, which is beneficial to prolonging the storage period of the rock slab glue.
[0029] In order to distinguish the filler in the synthetic component A from the filler in the component B, the former is defined as the first filler and the latter is defined as the second filler in the present invention. Unless otherwise specified, the first filler and the second filler should be independently understood as fillers.
[0030] In order to distinguish the thixotropic agent in component A from the thixotropic agent in component B, the former is defined as the first thixotropic agent and the latter is defined as the second thixotropic agent in the present invention. In the absence of specific reference, the first thixotropic agent and the second thixotropic agent should be independently understood as thixotropic agents.
[0031] The above substances can be used to obtain a rock slab adhesive with better comprehensive performance. Those skilled in the art can reasonably optimize and adjust the above ingredients according to the performance requirements of the rock slab adhesive.
[0032] According to the rock slab glue provided by the present invention, the weight ratio of component A to component B is 1:1.
[0033] Preferably, based on 100 parts by weight, the component A includes 55-65 parts of high-functionality acrylate, 5-10 parts of acrylate monomer, 1-2 parts of accelerator, 8-10 parts of diluent, 3-4 parts of first thixotropic agent and the balance of first filler.
[0034] Preferably, based on 100 parts by weight, the component B includes 54-56 parts of pentaerythritol tetrakis(3-mercaptopropionate), 14-16 parts of trimethylolpropane tris(mercaptopropionate), 6 parts of the second thixotropic agent and the balance of the second filler.
[0035] Further preferably, based on 100 parts by weight, the component A includes 65 parts of high-functionality acrylate, 5 parts of acrylate monomer, 1 part of accelerator, 9 parts of diluent, 4 parts of first thixotropic agent and the balance of first filler.
[0036] Further preferably, based on 100 parts by weight, the component B includes 56 parts of pentaerythritol tetrakis(3-mercaptopropionate), 14 parts of trimethylolpropane tris(mercaptopropionate), 6 parts of the second thixotropic agent and the balance of the second filler.
[0037] In a fourth aspect, the present invention also provides a method for preparing the rock slab glue as described above, wherein component A and component B are mixed and cured at a temperature of 5 to 25°C.
[0038] The preparation steps of the component A include: (1) mixing a high-functionality acrylate matrix, polypropylene glycol diacrylate, a diluent and an accelerator, dispersing them at 40-50° C. for 1-1.5 hours using a high-speed disperser until they are completely dissolved, and then cooling them to room temperature to obtain a premix; (2) mixing a first filler and a first thixotropic agent into the premix, dispersing them at a negative pressure of 0.05-0.1 MPa using a planetary mixer for 30-60 minutes until they are fully stirred and mixed, thereby obtaining component A. The preparation process of the component B is as follows: tetrakis(3-mercaptopropionic acid) pentaerythritol ester, trimethylolpropane tris(mercaptopropionate), the second filler and the second thixotropic agent are mixed, and dispersed for 30-60 minutes using a planetary mixer under a negative pressure of 0.05-0.1 MPa until they are fully stirred and mixed to obtain the component B.
[0039] The low-odor acrylate matrix for rock slab glue, rock slab glue and preparation method thereof provided by the present invention can take into account various application properties of the rock slab glue, especially high short-term bonding strength and good water resistance, by designing an acrylate matrix with a specific structure and using it in a two-component acrylate rock slab glue.
[0040] Furthermore, the curing system adopted by the rock slab glue provided by the present invention does not contain volatile irritating substances. By preferably using low-odor thiols and preferably acrylates and thiol curing accelerators, adjusting the combination of accelerators, thiols and acrylates, the curing speed is ensured while the odor of the prepared rock slab glue is much lower than that of rock slab glue products on the market. DETAILED DESCRIPTION
[0041] In order to make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be described clearly and completely below. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0042] If no specific techniques or conditions are specified in the examples, the techniques or conditions described in the literature in the field or the product instructions are used. If no manufacturer is specified for the reagents or instruments used, they are all conventional products that can be purchased through regular channels.
[0043] In order to obtain a high-functionality acrylate matrix with excellent performance, the present invention selected common monofunctional primary amines, difunctional primary amines, and trifunctional primary amines to conduct a large number of experiments, some of which are as follows: According to the formula in Table 1, dipentaerythritol hexaacrylate was added into a reactor equipped with a condensation reflux device, and reacted under a nitrogen atmosphere. The reaction system was heated to 50°C, and an amine chain extender was slowly added dropwise thereto. At the same time, the temperature was raised to 55°C and kept warm for 3.5 hours to obtain a high-functionality acrylate matrix.
[0044] Table 1
[0045] The high-functionality acrylate matrix prepared under the above-mentioned formula No. 1 to 13 was tested. The test method is: the high-functionality acrylate matrix, pentaerythritol tetrakis (3-mercaptopropionic acid) ester (thiol compound) and triethylenediamine (accelerator) are mixed at a fixed ratio of 100:100:1 by mass, and the performance of the obtained system is tested. Among them, the colloid feel is judged by stirring by professional technicians, and the mechanical property test adopts the JC / T 989-2006 non-structural load-bearing stone adhesive evaluation method. The short-term bonding strength is evaluated based on the JC / T 989-2006 standard with the curing period reduced to 30 minutes. The test results are shown in Table 2 below.
[0046] Table 2
[0047] From the above results, it can be seen that adding too much amine chain extender will lead to poor hand feel and poor construction performance (comparison of No. 3 and 4). Compared with monoamine chain extender, polyamine chain extender has poor construction performance, reduced wettability, stone-stainless steel compressive shear strength, and improved stone-stone compressive shear strength (comparison of No. 1, 2, 3, 5, 6, 7). By adjusting the ratio of monoamine and polyamine, hydroxyl-containing ethanolamine is preferred to improve the interfacial bonding strength, and alicyclic cyclohexanedimethylamine is preferred to improve the colloid strength. Among them, when the weight ratio of dipentaerythritol hexaacrylate: ethanolamine: 1,4-cyclohexanedimethylamine is 100:4:2 (No. 9), there is a better bonding effect.
[0048] Furthermore, the low-odor slate adhesive acrylate matrix, slate adhesive and preparation method thereof of the present invention are described in more detail through the following examples.
[0049] Embodiments 1 to 10 Embodiments 1 to 10 provide a rock slab adhesive, which is obtained by mixing component A and component B in a mass ratio of 1:1 at room temperature and curing.
[0050] Among them, the formula of component A is shown in Table 3 below, and the formula of component B is shown in Table 4 below.
[0051] The preparation process of component A is as follows: (1) a high-functionality acrylate matrix, polypropylene glycol diacrylate, a diluent and an accelerator are mixed, dispersed in a high-speed disperser at 45° C. for 1 hour until they are completely dissolved, and then cooled to room temperature to obtain a premix; (2) a first filler and a first thixotropic agent are mixed into the premix, dispersed in a planetary mixer at a negative pressure of 0.05 MPa for 45 minutes until they are fully stirred and mixed, thereby obtaining component A.
[0052] The preparation process of component B is as follows: tetrakis(3-mercaptopropionic acid) pentaerythritol ester, trimethylolpropane tris(mercaptopropionate), the second filler and the second thixotropic agent are mixed, and dispersed for 45 minutes using a planetary mixer under a negative pressure of 0.05 MPa until they are fully stirred and mixed to obtain component B.
[0053] Table 3
[0054] Table 4
[0055] Comparative Example 1 This comparative example provides a high-functionality acrylate matrix, which is based on the preparation process of the high-functionality acrylate matrix No. 9, wherein the mass of 1,4-cyclohexanedimethylamine and the like is replaced with T403 polyetheramine, and the obtained high-functionality acrylate matrix is recorded as the high-functionality acrylate matrix No. 14.
[0056] Furthermore, this comparative example also provides a rock slab adhesive, which differs from Example 1 only in that the high-functionality acrylate matrix No. 9 is replaced with the high-functionality acrylate matrix No. 14.
[0057] Comparative Example 2 This comparative example provides a high-functionality acrylate matrix, which differs from comparative example 1 in that the diluent is replaced by benzyl alcohol.
[0058] The rock slab glue prepared in Examples 1 to 10, the rock slab glue of Comparative Examples 1 and 2, and commercially available rock slab glue products were tested, wherein the odor level was tested according to HGT 4065-2008 adhesive odor evaluation method, the storage period was selected from products produced in the same period, and the test was carried out by placing them in an oven at 70°C for 720 hours, the feel of the colloid was judged by stirring by professional technicians, the mechanical properties were tested according to JC / T989-2006 non-structural load-bearing stone adhesive evaluation method, the short-term bonding strength was evaluated by shortening the curing period to 30 minutes based on the JC / T 989-2006 standard, the performance test items were selected and the test specimens were prepared according to industry standards, and the performance test results after complete curing are shown in Table 5 below.
[0059] It can be seen that the odor (environmental protection), colloid feel (constructibility), 30min stone-stone compressive shear strength (short-time rock adhesive bonding performance), 30min stone-stainless steel compressive shear strength (short-time rock adhesive bonding performance), stone-stone water immersion compressive shear strength (rock adhesive water resistance), impact toughness, and storage period of the low-odor acrylic rock adhesive prepared by Examples 1 to 10 of the present invention are not lower than or even higher than those of the prior art products (commercially available acrylic rock adhesive, commercially available epoxy rock adhesive, and commercially available unsaturated rock adhesive), and the odor (environmental protection) performance index has a more prominent advantage. Compared with Comparative Example 1, the embodiment of the present invention has a significant advantage in feel (constructibility), and compared with Comparative Example 2, the embodiment of the present invention has a significant advantage in storage period. On the whole, the comprehensive performance improvement effect of the low-odor acrylic rock adhesive prepared by the present invention is significant.
[0060] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A high-functionality acrylate matrix for rock slab adhesive, wherein the rock slab adhesive adopts a thiol-acrylate curing system, characterized in that: It is obtained by reacting dipentaerythritol hexaacrylate and an amine chain extender under heating conditions; The amine chain extenders include ethanolamine and cyclohexanedimethylamine.
2. The high-functionality acrylate matrix according to claim 1, characterized in that: The cyclohexanedimethylamine includes 1,4-cyclohexanedimethylamine; Preferably, the weight ratio of ethanolamine to cyclohexanedimethylamine is (4-5): (1-2); More preferably, the weight ratio of dipentaerythritol hexaacrylate, ethanolamine and cyclohexanedimethylamine is 100:4:
2.
3. The high-functionality acrylate matrix according to claim 1 or 2, characterized in that: Including one or a combination of two or more compounds having the structural formula R1-N(CH2-R2)2; R1 is selected from and / or ; R2 is selected from .
4. The method for preparing a high-functionality acrylate matrix according to any one of claims 1 to 3, characterized in that: include: Dipentaerythritol hexaacrylate and an amine chain extender are reacted under heating conditions; the amine chain extender comprises ethanolamine and cyclohexanedimethylamine.
5. A rock slab adhesive, obtained by mixing component A and component B and curing them, characterized in that: The component A comprises an acrylate matrix and an accelerator; the component B comprises a thiol compound; the accelerator comprises a tertiary amine structure; The acrylate matrix comprises the high-functionality acrylate matrix described in any one of claims 1 to 3 or the high-functionality acrylate matrix prepared by the preparation method described in claim 4.
6. The rock board glue according to claim 5, characterized in that: The thiol compound includes pentaerythritol tetrakis(3-mercaptopropionate) and / or trimethylolpropane tris(mercaptopropionate); Preferably, the weight ratio of pentaerythritol tetrakis(3-mercaptopropionate) to trimethylolpropane tris(mercaptopropionate) is (50-64):(6-20).
7. The rock board glue according to claim 5 or 6, characterized in that: Component A comprises 100 parts by weight: 55-70 parts of the high-functionality acrylate matrix, 0-10 parts of acrylate monomer, 1-4 parts of accelerator, 6-10 parts of diluent, 3-5 parts of the first thixotropic agent and the balance of the first filler; And / or, based on 100 parts by weight, component B includes 50-64 parts of pentaerythritol tetrakis(3-mercaptopropionate), 6-20 parts of trimethylolpropane tris(mercaptopropionate), 2-8 parts of the second thixotropic agent and the balance of the second filler.
8. The rock board glue according to claim 7, characterized in that: The acrylate monomer is selected from polypropylene glycol diacrylate; And / or, the accelerator is selected from one or a combination of two or more of triethanolamine, triethylenediamine and N,N-dimethylcyclohexylamine; And / or, the diluent is selected from one or a combination of two or more of nonylphenol, dodecylphenol and styrenated phenol; And / or, the first filler is selected from nano calcium carbonate; And / or, the first thixotropic agent is selected from hydrophobic fumed silica; And / or, the second filler is selected from nano calcium carbonate; And / or, the second thixotropic agent is selected from hydrophobic fumed silica.
9. The rock plate adhesive according to any one of claims 4 to 8, characterized in that: The weight ratio of component A to component B is 1:1; Preferably, based on 100 parts by weight, the component A includes 55-65 parts of high-functionality acrylate, 5-10 parts of acrylate monomer, 1-2 parts of accelerator, 8-10 parts of diluent, 3-4 parts of first thixotropic agent and the balance of first filler; Preferably, based on 100 parts by weight, the component B includes 54-56 parts of pentaerythritol tetrakis(3-mercaptopropionate), 14-16 parts of trimethylolpropane tris(mercaptopropionate), 4-6 parts of the second thixotropic agent and the balance of the second filler.
10. The method for preparing the rock plate adhesive according to any one of claims 5 to 9, characterized in that: Mix component A and component B at 5~25℃ and cure.